Grammatical and Lexical Errors in the Written English of Teacher Trainees: A Case Study of E.P. College of Education, Amedzofe - Akorli Innocent Selasie (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2025)
This qualitative case study investigates the grammatical and lexical errors in the writing of fifty final-year students at the E.P. College of Education, Amedzofe. Drawing on Corder's Error Analysis framework, student essays were analyzed to identify error types, frequencies, and their potential causes. Data were collected by simple random sampling from scripts anonymized and supplemented with self-reports on reading habits and mother tongue usage. The most frequent errors involved vocabulary misuse, tense, and structural flaws. These findings highlight the implications for English instruction and teacher training curricula. We recommend enhanced writing practice, improved entry standards, and promotion of reading and spoken English to improve students' written proficiency. The study contributes to the field of second language acquisition and offers pedagogical implications that can improve English language teaching in the Colleges of Education.